2016
DOI: 10.48550/arxiv.1607.03895
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tie-breaker: Using language models to quantify gender bias in sports journalism

Abstract: Gender bias is an increasingly important issue in sports journalism. In this work, we propose a language-model-based approach to quantify differences in questions posed to female vs. male athletes, and apply it to tennis post-match interviews. We find that journalists ask male players questions that are generally more focused on the game when compared with the questions they ask their female counterparts. We also provide a fine-grained analysis of the extent to which the salience of this bias depends on variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In addition, exploratory analysis utilizing t-SNE and vector arithmetic proved useful in identifying clusters of terms and users. Our methods contribute to growing literature on constructing language models to identify and unpack gendered phenomena; for instance, we can draw a parallel to models by Fu et al (2016) that found questions posed by journalists to professional female tennis players objectified women, while questions posed to male players were gamerelated, and by Way et al (2016), who found subtle gender inequalities in faculty hiring practices among universities of different rankings and career trajectories. Our methods can be generally applied to analyze the different user interaction patterns in any chat-based online platform.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, exploratory analysis utilizing t-SNE and vector arithmetic proved useful in identifying clusters of terms and users. Our methods contribute to growing literature on constructing language models to identify and unpack gendered phenomena; for instance, we can draw a parallel to models by Fu et al (2016) that found questions posed by journalists to professional female tennis players objectified women, while questions posed to male players were gamerelated, and by Way et al (2016), who found subtle gender inequalities in faculty hiring practices among universities of different rankings and career trajectories. Our methods can be generally applied to analyze the different user interaction patterns in any chat-based online platform.…”
Section: Discussionmentioning
confidence: 99%
“…We observed evidence for a male bias on the German speaking Web, i.e., for most of professions one can find much more sources for male than female professions. Moreover, several studies [10,25] reveal gender bias and stereotypes in mass media. I.e., apart from gender equality of the editor base, having transparent guidelines and rules towards representative equality in article content might prove just as useful to decrease gender disparities of individual articles; defining clear target audience groups and contemplating suitability of the content for those readers might likewise be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study by Fu, Danescu-Niculescu-Mizil, and Lee (2016), a public initiative that urges the media to focus on sports performance suggested that female athletes got more 'sexist commentary' and 'inappropriate interview questions' compared to their male colleagues, which was clearly visible in a video from 2015, which showed male athletes' awkward reactions to receiving questions that are usually posed to female athletes. However, their research results showed that the questions posed to male athletes were generally more game-related than those posed to female athletes (Fu, Danescu-Niculescu-Mizil, Lee, 2016). Furthermore, an analysis of online articles from 2009 discovered that more descriptors associated with the physical appearance and personal lives pertain to male basketball players, as compared to female ones.…”
Section: Language Gender and Sportsmentioning
confidence: 99%